The Impact of Maternal Weight With Fetal Outcome; A Cohort Study In An Underdeveloped Region Of Pakistan - Momina, Shahzad Bashir; Mushtaq, Naila; Butt, Suniya Arshad; Nawaz, Sobia; Asad, Ayesha; Syed, Shazia (Journal of Rawalpindi Medical College, 2024)
Objective: This study has been conducted to observe the association of maternal weight with fetal outcomes among women in an underdeveloped region of interior Sindh. Methods: This was an observational study conducted at CMH Hospital Choor, from 1st November 2021 to 30th April 2022, on 84 pregnant women. All antenatal women as early as 16 weeks presented for antenatal visits, were included. Their BMI (body mass index) was calculated. Their increase in weight during pregnancy was noted. Any pre-existing medical complications (hypertension) antenatal or intrapartum complications (including Anemia, Preterm labour, IUGR, and fetal distress) were noted in the mother. The fetal APGAR score was calculated. The passage of meconium and, the need for NICU admission were noted. Results: There is a positive but insignificant and weak correlation between maternal and birth weight using Pearson correlation analysis. The correlation between the above two variables is 0.069 which is positive but weak. It was found that there was a significant association between low maternal weight and NICU admission of the baby at delivery, p-value < 0.05. There were 33 cases (39%) with low maternal weight of 35-46kg and 51 (61%) cases with normal weight of 47-58 kg. There was only one case of meconium aspiration. Conclusion: Women who had low BMI during the antenatal period were observed to be associated with increased morbidity and poor perinatal outcome of the fetus in terms of poor APGAR score, meconium staining and need for NICU admission. Keywords: BMI, IUGR, preterm labour, meconium staining, APGAR score